Paralelos entre ação teatral e direcionalidade musical - Ernesto Gomes Valenca (2010)
This dissertation aims to investigate the historical parallel of theater and music in the period of constitution to the breakdown of drama and the tonal system. The central point of discussion is the analogy between the concepts of theatrical action and musical directionality, understood as the unfolding of a material initially selected as a basis for artistic creation from the elements intrinsic to the same material, setting up a similar field between theater and music. Such similar field is fully developed in the drama and the tonal system, through the establishment of dialectical structures of causality, which confer a high degree of autonomy to the two languages. It was shown the exploration of the limits of tonality and drama by playwrights and composers of the late nineteenth and early twentieth century, bringing on a crisis in the two artistic forms that leads to question the need for causality and to new settings theater and music in later times.